Joan is okay : a novel - Wang, Weike (Random House, 2022)
"Joan is a thirtysomething ICU physician at a busy New York City hospital, the daughter of Chinese parents who moved to America to secure the American dream for Joan and her brother, Fang, then returned to China. Joan's whole life has been about study and work. She logs excessive hours at the hospital, exhibits little interest in having friends, let alone lovers, and her medical colleagues sometimes resent her, misreading dedication to work as ambition. Sometimes Joan looks up and wonders where her true roots lie: at the hospital, where her white doctor's coat makes her feel at home; or with her family, who try to shape her life by their own social and cultural expectations. But when Joan's father suddenly dies, her mother returns to America, now more determined than ever to connect with Joan while staying with Fang on his sprawling Greenwich estate. The hospital, and life on the Upper West Side of New York City, provide cover, and protection--for a while. But then a compelling new neighbor moves in to the apartment next door, and Joan is unwillingly drawn into the social lives of people she's been happily ignoring for years. And at the hospital, a new HR "wellness initiative" about work/life balance forces Joan to take a mandatory leave of absence; she's barred from the hospital and life as she knows it. When she decides to decamp to Fang's, and to her newly reconstituted family, her family tries to reorder her life, threatening the parameters she'd carefully calibrated--until the day she must return to the city to face a crisis larger than anything she's encountered"--